2012
DOI: 10.5539/ijbm.v7n21p78
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Influences on Consumer Behaviour

Abstract: This study investigates the differences between individualism-collectivism and consumer behaviour in relation to automobile purchases. In this study the author looked at several stages of the consumer decision-making process and identified the possible differences between individualist and collectivist consumers and how it influences purchase decision. Based on a sample of 211 respondents from individualist (Australian-born) and collectivist (Asian-born) backgrounds, an established scale (Cultural Values Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 60 publications
(50 reference statements)
2
40
0
1
Order By: Relevance
“…This means that the estimated regression model is feasible, with a simultaneous contribution of 83.5%. This finding supports Lusardi & Mitchell (2010), Chen and Volpe (2002), Lutfi & Iramani (2008), Setiadi, (2013), , Kotler and Keller (2006), Inderjeet Sethi and AS Chawla (2014), Nayeem, Tahmid (2012) who revealed that consumption behavior is generally influenced by factors explained in this research. Empirical results describe that financial literacy, social and cultural factors give a real contribution to consumer consumption behavior.…”
Section: Discussionsupporting
confidence: 84%
“…This means that the estimated regression model is feasible, with a simultaneous contribution of 83.5%. This finding supports Lusardi & Mitchell (2010), Chen and Volpe (2002), Lutfi & Iramani (2008), Setiadi, (2013), , Kotler and Keller (2006), Inderjeet Sethi and AS Chawla (2014), Nayeem, Tahmid (2012) who revealed that consumption behavior is generally influenced by factors explained in this research. Empirical results describe that financial literacy, social and cultural factors give a real contribution to consumer consumption behavior.…”
Section: Discussionsupporting
confidence: 84%
“…Culture is one of the most important aspects that determine brand fondness and consumer behavior. People of the same culture also share language, behavioral patterns, and values (Cobb-Walgren et al, 1995;Nayeem, 2012). Hence, it is easier to build communication at a general, rather than at an individual level (Nayeem, 2012).…”
Section: Perceptional Components Of Brand Equitymentioning
confidence: 99%
“…People of the same culture also share language, behavioral patterns, and values (Cobb-Walgren et al, 1995;Nayeem, 2012). Hence, it is easier to build communication at a general, rather than at an individual level (Nayeem, 2012). However, buying intentions and the reasons that consumers choose a specific product reflect their behavior, either individually or as a group.…”
Section: Perceptional Components Of Brand Equitymentioning
confidence: 99%
“…This renewed interest in branding and strategy has also triggered researchers to study universities as brands (Nayeem (2012). This study benefits to researchers in the future about the effect of consumer decision making in the context of improving brand awareness.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Brand Awareness is buyer aware of the existence of the brand but the knowledge about it is limited and obviously has no particular emotional attachment to it as a result he may or may not think of purchasing the brand (Nayeem, 2012).Brand awareness does not mean to merely know the name of the brand or to have seen it before, it rather means that consumer can associate the name, logo and something similar in his mind (Yildram, 2010).…”
Section: Brand Awarenessmentioning
confidence: 99%